Insight Into Alignment Between Compensation Strategy and Business Strategy in Selected Croatian Companies - Danica Bakotić; Ivana Načinović Braje (European Scientific Journal, ESJ, 2017)
This paper deals with the relationship between compensation strategy and business strategy in Croatian companies. It is the first output of a large investigation into compensation management practice and possibilities for its improvement in Croatia. The findings of this paper result from the Delphi method conducted on experts from 13 selected companies. The research results suggested that there is no alignment between compensation strategy and business strategy in Croatian companies. The reasons for this are: lack of clearly defined functional strategy and lack of management engagement in aligning these strategies; unclear company objectives and strategies, as well as frequent changes in business strategy; collective labour agreements and lack of the autonomy of the HR departments. The experts in Croatian companies consider that compensation strategy can impact on firm’s competitiveness through improved employee loyalty and satisfaction; motivation and performance; attracting high quality employees and improved employee image. Research results also identified the obstacles for implementing contemporary compensation management mechanisms in Croatian companies. The general conclusion of this paper is that in Croatian companies there is a much room for improvement in the domain of alignment between compensation strategy and business strategy and for the introduction of contemporary compensation management practices.